Relationships among classifications of ayurvedic medicine diagnostics for imbalances and western measures of psychological states: An exploratory study - Paul J. Mills; Christine Tara Peterson; Kathleen L. Wilson; Meredith A. Pung; Sheila Patel; Lizabeth Weiss; Suhas G. Kshirsagar; Rudolph E. Tanzi; Deepak Chopra (Journal of Ayurveda and Integrative Medicine, 2019)
Background: According to Ayurveda, the traditional medical system of India, doshas are a combination of characteristics based on a five-element philosophy that drive our mental and physical tendencies. When the doshas, or functional principles, are out of balance in quality or quantity, wellbeing is adversely affected and symptoms manifest. Objective: This study examined relationships among imbalances in the doshas (termed Vikruti) reported via questionnaire and Western measures of psychological states. Materials and methods: Study participants were 101 women (n = 81) and men (n = 20), mean age 53.9 years (SD = 11.7; range 32–80). Participants completed questionnaires to categorize their Vikruti type and psychological states, which included depressed mood (CESD), anxiety (PROMIS), rumination & reflection (RRQ), mindfulness (MAAS), stress (PSS), and quality of life (Ryff). Results: Multivariate general linear modeling, controlling for age, gender and body mass index (BMI), showed that Vata imbalance was associated with more anxiety (p ≤ 0.05), more rumination (p ≤ 0.01), less mindfulness (p ≤ 0.05), and lower overall quality of life (p ≤ 0.01). Pitta imbalance was associated with poorer mood (p ≤ 0.01) and less mindfulness (p ≤ 0.05), more anxiety (p ≤ 0.05) and stress (p ≤ 0.05). Kapha imbalance was associated with more stress (p ≤ 0.05), more rumination (p ≤ 0.05) and less reflection (p ≤ 0.05). Conclusion: These findings suggest that symptoms of mind-body imbalances in Ayurveda are differentially associated with western assessments of psychological states. Ayurvedic dosha assessment may be an effective way to assess physical as well as emotional wellbeing in research and clinical settings. Keywords: Vikruti, Dosha, Mood, Anxiety, Quality of life